2020
DOI: 10.1371/journal.pone.0234852
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of leisure time and household physical activity and the risk of mortality among middle-aged Korean adults

Abstract: Background Although many studies have focused on leisure time physical activity (LTPA), household physical activity (HPA) can contribute to health benefits. This study aimed to compare LTPA and HPA patterns and to examine the association of these types of activities with the risk of mortality in Korea. Methods A total of 125,299 participants 40 to 69 years old and enrolled in the Health Examinees (HEXA) study from 2004 to 2012 were included in this study. The sex-specific LTPA and HPA categories were defined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
1
12
0
1
Order By: Relevance
“…Our findings showed that every 1 MET-h/week increment of the housework was associated with a decreased risk of allcause mortality, which was consistent with the previous studies (31)(32)(33). In addition, our results were like previous studies (34 -36), which found that performing brisk walking/health exercises/Yangko was associated with a lower risk of mortality.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings showed that every 1 MET-h/week increment of the housework was associated with a decreased risk of allcause mortality, which was consistent with the previous studies (31)(32)(33). In addition, our results were like previous studies (34 -36), which found that performing brisk walking/health exercises/Yangko was associated with a lower risk of mortality.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to Japan, Korea’s rates of exercise participation in the general population are similar to rates reported in western countries. 32 Interestingly, whereas approximately 50% of adults who live with a SCI in western countries do not participate in any leisure-time physical activity (LTPA; e.g. 33 , 34 ), a small study (n=79) reported just 4% of Koreans with SCI did no LTPA whatsoever.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of chores and yard work failed to attain moderate-intensity level in over 80% of the respondents thereby indicating the need to engage more in yard work because it is more energy-consuming. This is important because reports have shown that household work PA can attain moderate intensity levels (>600 METmins/week) or 150 mins/week (Phongsavan et al 2004;Murphy et al 2013;Park et al 2020). Some background characteristics tend to influence performance of household chores and yard work as indicated by the chi square analysis and the variations in the prevalence of low and moderate-intensity PA.…”
Section: Discussionmentioning
confidence: 99%